2021
DOI: 10.5114/aoms.2020.93739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free and nanoparticulate curcumin on chemically induced liver carcinoma in an animal model

Abstract: Introduction Curcumin therapeutic applications are constrained by its prominent metabolic instability as well as inadequate absorption and bioavailability. The current study was designed to enhance the curcumin bioavailability by exploiting nanoparticles. Material and methods Eleven groups of mice were divided into: normal and nanoparticle control groups, a hepatocellular carcinoma (HCC) group induced by diethylnitrosamine (DEN), 2 groups treated with DEN plus a high do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…Furthermore, PIP-loaded BLs exhibited the highest selectivity index against Huh-7 cells (420.55 vs. 18.959 for the CU suspension and 20.82 for Dox) ( Figure 7(C) ). These results are in accord with those of Mohammed et al., who reported that both CU-loaded nanoparticles and CU suspension reduced chemically induced hepatocellular damage in hepatocellular carcinoma (Mohammed et al., 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, PIP-loaded BLs exhibited the highest selectivity index against Huh-7 cells (420.55 vs. 18.959 for the CU suspension and 20.82 for Dox) ( Figure 7(C) ). These results are in accord with those of Mohammed et al., who reported that both CU-loaded nanoparticles and CU suspension reduced chemically induced hepatocellular damage in hepatocellular carcinoma (Mohammed et al., 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…It is also worth mentioning that curcumin has other effects as well, such as anti-cancer properties. It is therefore a nutraceutical with great prophylactic and therapeutic potential, not only in the management of ASCVD ( 141 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCC, the foremost dominant sort of liver cancer, is that the third leading explanation for cancer mortality around the world, with quite 500,000 people affected every year (El-Ahwany et al, 2019, Mohammed et al, 2021). HCC can be treated in a variety of ways.…”
Section: Discussionmentioning
confidence: 99%